2012
DOI: 10.1007/s00221-012-3360-9
|View full text |Cite|
|
Sign up to set email alerts
|

The impacts of coordinative exercise on executive function in kindergarten children: an ERP study

Abstract: This study examined the behavioral and neuroelectrical impacts of a coordinative exercise intervention with different exercise intensities on executive function in kindergarten children. Participants underwent the Eriksen flanker test before and after an exercise program that involved 35-min sessions twice per week for 8 weeks, with either low or moderate intensity. Our findings revealed that exercise intervention, regardless of intensity, resulted in shorter reaction times and higher response accuracy in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 45 publications
11
136
1
6
Order By: Relevance
“…Sample sizes have ranged from 20 to 1,274, with students ranging in age from six to 13 years. Findings from studies conducted in laboratory settings (n=9) are mixed, with three failing to definitively support (45, 62, 152) and six supporting (11, 31, 61, 66, 86, 160) beneficial effects on tasks that measure both speed and accuracy. All of the studies supporting beneficial effects used a version of the flankers test or a measure of choice reaction time for their cognitive measure.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes have ranged from 20 to 1,274, with students ranging in age from six to 13 years. Findings from studies conducted in laboratory settings (n=9) are mixed, with three failing to definitively support (45, 62, 152) and six supporting (11, 31, 61, 66, 86, 160) beneficial effects on tasks that measure both speed and accuracy. All of the studies supporting beneficial effects used a version of the flankers test or a measure of choice reaction time for their cognitive measure.…”
Section: Resultsmentioning
confidence: 99%
“…Tests of executive function indicated that overweight children derived the greatest gains in inhibitory efficiency but only if they participated in the enhanced training program. In a similar study, Chang et al 39 developed a soccer-based coordinative exercise program for kindergarten children. The intervention consisted of either low-or moderate-intensity exercise sessions that took place for 35 min, twice a week for 8 weeks.…”
Section: Chronic Qualitative Exercise Interventionsmentioning
confidence: 97%
“…In general, these studies have revealed that exercise improves cognitive processes, such as attention and speed of processing, but that the improvement lessens shortly after the exercise ends (e.g., Budde, VoelckerRehage, Pietrabyk-Kendziorra, Ribeiro, & Tidow, 2008;Hillman, Snook, & Jerome, 2003). Other studies have tested participants after a relatively long period (weeks or months) of physical training and compared their performance with that of a control group who did not train during that time (Chang, Tsai, Chen, & Hung, 2012;C. L. Davis et al, 2007), also revealing executive function improvements in participants who performed the exercise training.…”
Section: Dva In Young Martial Arts Athletes and Nonathletesmentioning
confidence: 99%